Effect of whey goat milk kefir on hydrophobicity of E. coli O157:H7, S. typhi bacteria and C. albicans - Dedi Fardiaz; Lilik Eka Radiati (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2012)
The hydrophobicity of bacteria. was determined using BATH (Bacteria adhesion to hydrocarbon) test. All bacteria showed that 0,9 ml n-octane exposure gave a positive response and indicating that E. coli O157:H7 was categorized as moderate hydrophobic bacteria,  while S.  typhi  and C. albicans were catagorized as  highly hydrophobic bacteria. Goat Milk Kefir increased hydrophobicity of E.  coli O157:H7 by 24.40, however, decreased hydrophobicity of S. typhi by 47.56  and C. albicans by 70.14 percent, respectively. This finding showed that one of the inhibition mechanism may be caused by  an interaction  of  organic acid and peptide  compounds with cell membrane, in which hydrophobic sites of component  modified the hydrophobicity of the bacteria cell surface. The hydrophobicity modification in bacterial  cell wall might result inhibition of adhetion bacteria at cell host. Key words : Enterophatogenic bacteria, hidrophobisitas bacteria